Otter country : an unexpected adventure in the natural world - Darlington, Miriam (Tin House, 2024)
"Mysterious, graceful, and ever-clever, otters have captivated our imaginations despite the fact that few people have encountered one in the wild. In Otter Country, celebrated nature writer Miriam Darlington captures the fascination she's had for these playful animals since childhood and chronicles her immersive journey into their watery world. Over the course of a single year, Darlington takes readers on a winding expedition in pursuit of these elusive creatures-from her home in Devon, England, through the wilds of Scotland, Wales, the Lake District, and the countryside of Cornwall. As she's drawn deeper into wilder habitats, trekking through changing landscapes, seasons, and weather, Darlington meets biologists, conservationists, fishing and hunting enthusiasts, and poets-enriching her understanding, admiration, and awe of the wild otter. With each encounter, she reveals the scientific, environmental, and cultural importance of this creature and the places it calls home. Full of wonder, hope, and an abiding love for the natural world, Otter Country: An Unexpected Adventure in the Natural World is a beautiful and captivating work of nature writing, pursuing one of nature's most endearing and endlessly fascinating creatures"--